2020
DOI: 10.18502/ijm.v12i2.2612
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, clinical findings and laboratory parameters in neonates with acute bacterial meningitis

Abstract: Background and Objectives: Neonatal meningitis is one of the most important and serious neonatal infections with a high mortality and morbidity rate. The present study aimed to investigate the causes, clinical signs, laboratory parameters and mortality rates in newborns with bacterial meningitis. Materials and Methods: This cross-sectional study was performed on 468 neonates aged 2-28 days admitted to NICU in Ghaem Hospital Mashhad, Iran by available sampling method during 2009-2018. Meningitis was confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The results of our study showed that both Gram-negative (73.7%) and Gram-positive (26.3%) bacterial isolates were responsible for NBM, with K. pneumoniae (36.8%), NLF-GNR (21%), and GBS (15.8%) were the leading bacterial isolates. Similar to our finding, hospital-based studies from Mexico 35 and Iran 36 , 37 reported K. pneumoniae as the leading cause of NBM. Bacteria in the Enterobacteriaceae group, including K. pneumoniae , are known to cause nosocomial infections in neonates.…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study showed that both Gram-negative (73.7%) and Gram-positive (26.3%) bacterial isolates were responsible for NBM, with K. pneumoniae (36.8%), NLF-GNR (21%), and GBS (15.8%) were the leading bacterial isolates. Similar to our finding, hospital-based studies from Mexico 35 and Iran 36 , 37 reported K. pneumoniae as the leading cause of NBM. Bacteria in the Enterobacteriaceae group, including K. pneumoniae , are known to cause nosocomial infections in neonates.…”
Section: Discussionsupporting
confidence: 92%
“…A literature review of reports concerning patients with congenital dermal sinus disease who developed abscesses showed similar causative bacteria; however, there were no cases linked to Enterobacter aerogenes [8] . Meningitis due to Enterobacter aerogenes has been reported only in specific conditions, such as patients undergoing neurosurgical procedures [9] , [10] , [11] and neonates in the NICU [3] . In the present case, we considered that the hematogenous infection was negative, since the blood culture was negative.…”
Section: Discussionmentioning
confidence: 99%
“…cause opportunistic and nosocomial infections in the intensive care unit (ICU) [2] . Moreover, pediatric meningitis due to Enterobacter aerogenes has been reported in neonates in the neonatal ICU (NICU) [3] . However, community-acquired infections due to Enterobacter aerogenes associated with congenital dermal sinus in non-neonates have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 K. aerogenes is known to cause nosocomial pneumonia, urinary tract and bloodstream infection in adults, especially immunocompromised and intensive care patients [4][5][6] but can also lead to necrotizing enterocolitis, meningitis or sepsis in preterm infants. [7][8][9][10] Unlike other Enterobacteriaceae, K. aerogenes rarely causes outbreaks in neonatal intensive care units (NICU). Some NICU outbreaks with K. aerogenes have been reported previously, causing substantial morbidity and mortality.…”
mentioning
confidence: 99%
“…3,4 K. aerogenes is known to cause nosocomial pneumonia, urinary tract and bloodstream infection in adults, especially immunocompromised and intensive care patients 4–6 but can also lead to necrotizing enterocolitis, meningitis or sepsis in preterm infants. 7–10…”
mentioning
confidence: 99%